SISTEM PENGAMAN SEPEDA MOTOR MENGGUNAKAN E-KTP BERBASIS ARDUINO UNO - Prasetyo Adi Nugroho (Institut Teknologi dan Bisnis Swadharma, 2022)
In the era of globalization, security system technology is very important. Motorcycles are vulnerable to theft because they still use manual locks. One of them is the safety system on motorcycles that has developed very rapidly. But the security system used on motorcycles today is still not safe enough because it still has weaknesses that can be used by criminals to steal motorcycles. Therefore, a better additional safety system is required on the vehicle itself and is easy to use by the vehicle owner. Therefore, a better additional safety system is required on the vehicle itself as well as easy to use by the vehicle owner. One of the tools that can be used to help meet the security system is to use E-KTP with RFID (Radio Frequency Identification) technology. This research aims to design an additional safety system of Arduino Uno-based motorcycles that can be used to maintain motorcycle safety